Fault-Tolerant Control With Active Fault Diagnosis for Four-Wheel Independently Driven Electric Ground Vehicles - Wang, Rongrong; Wang, Junmin (IEEE transactions on vehicular technology, 2011)
This paper presents a fault-tolerant control approach for four-wheel independently driven (4WID) electric vehicles. An adaptive control-based passive fault-tolerant controller is designed to ensure vehicle system stability and to track the desired vehicle motion when an in-wheel motor/motor driver fault happens. Due to the system actuation redundancy, it is challenging to isolate the faulty wheel and to accurately estimate the control gain of the faulty in-wheel motor/motor driver for 4WID electric vehicles. An active fault diagnosis (FD) approach is thus proposed to explicitly isolate and evaluate the fault. Based on the estimated control gain of the faulty wheel, the control efforts of all the wheels are redistributed to relieve the torque demand on the faulty wheel. Simulations using a high-fidelity CarSim full-vehicle model show the effectiveness of the proposed in-wheel motor/motor driver active fault diagnosis and fault-tolerant control approaches in various driving scenarios.